2016
DOI: 10.1186/s12986-016-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Replacing carbohydrate with protein and fat in prediabetes or type-2 diabetes: greater effect on metabolites in PBMC than plasma

Abstract: BackgroundActive metabolism of peripheral blood mononuclear cells (PBMC) could suggest their suitability for metabolomics studies. This study examined whether reductions in PBMCs and plasma lipoprotein-associated phospholipase A2 (Lp-PLA2) activities induced by dietary intervention affected the overall metabolic profiles of PBMC and plasma.MethodsEighty nonobese subjects aged 40–70 years (18.5 ≤ BMI < 30 kg/m2) with prediabetes or newly-diagnosed type-2 diabetes were assigned to consume either the usual refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The detailed methods for sample preparation and analysis using ultraperformance liquid chromatography (UPLC)-linear-trap quadrupole (LTQ)-Orbitrap mass spectrometry (MS), data processing, and putative identification of serum metabolites were reported in a previous study (14).…”
Section: Nontargeted Metabolic Profiling Of Serummentioning
confidence: 99%
“…The detailed methods for sample preparation and analysis using ultraperformance liquid chromatography (UPLC)-linear-trap quadrupole (LTQ)-Orbitrap mass spectrometry (MS), data processing, and putative identification of serum metabolites were reported in a previous study (14).…”
Section: Nontargeted Metabolic Profiling Of Serummentioning
confidence: 99%
“…LysoPC was involved in several possible pathways: (1) LCAT and oxidation of LDL production, (2) hepatocyte secretion, and (3) platelet activation and deletion of the LDL receptor [17]. Changed LysoPC concentrations have been found in cancers [18][19][20][21][22][23][24], inflammatory disorders [25], mitochondrial disease [26], Alzheimer's disease [27], diabetes [28][29][30][31], and acute coronary syndrome [17]. Nowadays, many researches showed that LysoPC18:0 concentration was associated with cancer risk [20][21][22][23]32] and mitochondrial disease [26]; meanwhile, studies on the association between LysoPC18:0 and diabetes [29][30][31] or CVD/AMI/acute coronary syndrome [17] are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected following an overnight fast of at least 12 hours. The levels of fasting triglycerides, total cholesterol, HDL‐cholesterol, LDL‐cholesterol, glucose, and insulin and the LDL particle size were measured using previously described methods . Insulin resistance (IR) was calculated as follows: the homeostasis model assessment (HOMA)‐IR = (fasting glucose [mmol/L] × fasting insulin [μIU/mL])/22.5.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of fasting triglycerides, total cholesterol, HDL-cholesterol, LDL-cholesterol, glucose, and insulin and the LDL particle size were measured using previously described methods. 10 Insulin resistance (IR) was calculated as follows: the homeostasis model assessment (HOMA)-IR = (fasting glucose [mmol/L] × fasting insulin [μIU/mL])/22.5. The apoA-I concentrations in serum were measured using a specific antiserum (Roche, Basel, Switzerland), and the apoA-V concentrations in plasma were assessed via a Human Apolipoprotein A5 ELISA Kit (Cusabio, Zhejiang, China).…”
Section: Clinical and Biochemical Assessmentsmentioning
confidence: 99%